A Novel High Voltage Gain Buck-Boost Converter with Dual Mode Boost - Mustafa Okati; Mahdiyeh Eslami; Mahdi Jafari Shahbazadeh (Majlesi Journal of Electrical Engineering)
This paper focuses on introducing a transformerless DC/DC converter with low total switching device power in dual working modes including step-up and step-up/down modes. The proposed converter is analysed in terms of the continuous conduction mode, steady state, and efficiency with the replacement of parasitic resistance effects. The proposed converter in the step-up mode has a high voltage gain ratio and a continuous input current. Then, the other working mode of the proposed converter with relevant DC/DC converters is compared. By this comparison, the proposed converter has a high voltage gain ratio. Also, the converter characteristics such as voltage stress on power switches and charge pump capacitors are in a good condition in this mode. Finally, the experimental results from a laboratory made prototype and the obtained waveforms from the simulation in PLECS are presented for validation such as higher voltage gain ratio, lower total switching device power and better efficiency.